Negative sequence compensation control strategy for electrified railways with super-capacitor integrated MMC - LUO Zhongyou; ZHAO Puzhi; DUAN Yu; QIN Yanhui; CHEN Tianshu (机车电传动)
In order to solve the power quality issue caused by dominant negative sequences, which result from single-phase loads of electrified railways in the three-phase grids, this paper presented a control strategy of compensation for negative sequences particularly suitable for electrified railways, taking the super-capacitor integrated modular multilevel converter (SC-MMC) system as the object, and leveraging precise compensation of negative sequence current by converters and efficient utilization of regenerative braking energy through energy storage facilities as the regulation means. Aimed to improve system reliability and flexibility, the MMC sub-modules were connected with super-capacitor storage devices in a decentralized pattern, to coordinate the MMC and energy storage devices for joint negative sequence compensation. This study began with an analysis of the working theory of the energy storage modular multilevel system, based on the main circuit topology and negative sequence compensation principle. Then, a system mathematical model was constructed based on a single-phase equivalent circuit and working modes were divided into charging, discharging, and balancing, taking into account the locomotive load characteristics and super-capacitor state of charge (SOC). Finally, a hierarchical coordinated control strategy was proposed, among which energy management is designed at the upper layer to identify working modes and calculate reference power for each port within the limits specified in relevant national standards, while port current control was designed at the lower layer to enable power tracking for each port and dynamic switching coordination between different operating modes. The case study shows the effectiveness of the SC-MMC system in compensating for negative sequences in the grid under different locomotive load levels and super-capacitor SOC scenarios, and coordinated control of the super-capacitor and MMC to contribute to compensation.